Characteristics, sources, and health risks of PM2.5-bound trace elements at a national park site in southern China - Ding, Runping; Cheng, Zhenyu; Xing, Jiaoping; Chen, Feifeng; Zhang, Yangwen; Wang, Yan; Wang, Wenhua; Song, Xiaoyan; Ye, Qing; Zhang, Linping; Liu, Yuanqiu (Scientific reports, 2025)
The health effects of trace elements in PM 2.5 have been the subject of widespread public concern. In this study, the 18 trace elements in PM 2.5 samples collected at a national park were measured to analyze their concentrations, sources, and health risks. The results showed that the average concentration of 18 trace elements was 191.99 ng/m 3 (0.89-1638.28). Higher concentrations of crustal elements are associated with northwestern air masses and southeastern air masses, while higher concentrations of anthropogenic elements are associated with southwestern air masses. The total non-carcinogenic risk of the harmful elements was below the acceptable threshold, for both adults (0.723) and children (0.448). The total carcinogenic risk of the hazardous elements was above the safe level for both adults and children, and the carcinogenic risk of the hazardous elements is As > Ni > Cr > Pb. Natural sources, vehicle emissions, coal combustion, biomass combustion, and industrial sources were identified by both the Absolute Principal Component Score-Multiple Linear Regression (APCS-MLR) model and the Positive matrix factorization (PMF) model. Both the APCS-MLR-HRA model and the PMF-HRA model indicated that vehicle emissions and industrial sources were the main contributors to non-carcinogenic risks, while industrial and coal combustion sources were the main contributors to carcinogenic risks. Mn was the main contributor to the non-carcinogenic risk, while As was the main contributor to the carcinogenic risk. Mn and As should be prioritized as control elements to address the higher non-carcinogenic and carcinogenic risks from vehicle emissions, industrial, and coal combustion sources.